The personality profile of ultimate frisbee players based on gender - Piepiora, Paweł; Sadowska, Monika; Supiński, Jan (Quality in Sport, 2020)
The aim of the study was to try to determine the personality of the ultimate frisbee players. The following hypothesis was accepted for verification: the personality profile of the ultimate frisbee players is similar to the profile of players practicing the same sport. The subjects of the cognitive experiment were people training ultimate frisbee (N = 60), including thirty men (n = 30) and thirty women (n = 30). The research was conducted using the NEO-FFI questionnaire. It has been shown that the personality profile of ultimate frisbee players differs in the scale of neuroticism. Women had a higher level of neuroticism than men. And the sten interpretation of the results showed that people training ultimate frisbee regardless of gender are characterized by average personality indicators.